An integrated marketing communication campaign for Solstice by Ilustrado - Pimentel, Katrina Espineli (Animo Repository, 2017)
Solstice by Ilustrado, a merger of two great culinary brands, offers a fusion of modern continental and heritage Filipino-Spanish cuisines. It brought together the rich history and heritage and the modern culinary twist with its reinvented menu. The refreshed menu is complemented with a carefully chosen selection of fine wines to complete the gastronomic experience it offers to its enlightened market. Aside from its premium food and wine offerings, it boasts on its impeccable service and impressive ambience to cater and satisfy the enlightened taste of todays modern Ilustrados. The meaning of Solstice and Ilustrado embodies a mix of culture, taste, heritage and sophistication. Although it manifests an elite persona, it still shows that dining at Solstice by Ilustrado is a complete and enlightened dining experience. This integrated marketing communication campaign aims to develop the brand name of Solstice by Ilustrado and to create brand loyalty by highlighting the overall gastronomic dining experience it offers through its premium food and wine offerings, impeccable service and impressive ambience. The campaign will run for a nine month period starting in April 2017 until December 2017 with a proposed budget of Php 6.7 million covering public and media relations, print, digital, events, promotions, direct marketing and out-of-home touchpoints. A continuing plan is recommended for year 2018 to further push and uplift brands equity and an evaluation after the campaign should be done to better re-align the campaign if needed and necessary.